Links between the economy competitiveness and logistics performance in the Visegrád Group countries: Empirical evidence for the years 2007-2018 - Botond Kálmán; Arnold Tóth (Entrepreneurial Business and Economics Review (EBER), 2021)
Objective: The objective of the article is to examine the relationship of competitiveness and logistics performance and - on the basis of this relationship - inspect which of the 12 pillars of the Global Competitiveness Index (GCI) reveal developments in the logistics performance of Visegrád Group (V4) countries. Next, we analyse the possibility of creating a common indicator number, by which the index formulated based on the GCI pillars and the Logistics Performance Index (LPI) values can simultaneously express competitiveness and logistics development level. Research Design & Methods: For our research, we used the time series from the Logistic Performance Index published every three years by the World Bank and the Global Competitiveness Index annually published by the World Economic Forum. We analysed the correlation between the pillars of the GCI and the index components of the LPI and then chose pillars that make it apparent how competitiveness determines the development level of logistics. To that end, we first used the Pearson correlation coefficient and, later, structural equation modelling. We performed the examination of the logistics development level of V4 countries based on the competitiveness pillars by objective index values, but also by comparison to countries that are on top of the LPI ranking. Findings: Institutions, adoption of information and communication technology (ICT), and Innovation have the most defining effect on logistics performance in V4. The countries of V4 were successful in improving the performance level of their logistics sector, but the performance of Poland and the Czech Republic exceeds the performance of Slovakia and Hungary in practically all of the studied areas. Implications & Recommendations: The present study primarily highlights the fact that further efficient development can only be realised by appropriately harmonising the activities of economic policymakers and actors. The examined V4 countries showed similar development levels, so we also gave them similar suggestions, which mainly include the development of the info-communication sector and the improvement in the effectiveness of the Institutions competitiveness pillar. Contribution & Value Added: The last time V4 countries logistics capabilities were scrutinised was in 2015. Since then, the pillar structure of the World Economic Forum underwent a significant change. This study examines the group's logistics performance by using more up-to-date data and highlighting the way for further research activities by searching for comparative advantages, which may allow V4 countries to further increase their competitiveness and logistics performance.
Keywords: F63; P25; P27; R11; 330; competitiveness; logistics; performance; The Visegrad Group; development